2010
DOI: 10.1186/1476-511x-9-90
|View full text |Cite
|
Sign up to set email alerts
|

The Gln27Glu Polymorphism in β2-Adrenergic receptor gene is linked to hypertriglyceridemia, hyperinsulinemia and hyperleptinemia in Saudis

Abstract: Backgroundβ2-adrenoceptor (β2AR) gene polymorphism glutamine 27 glutamic acid (Gln27Glu) and Arg16Gly were reported to have an association with obesity and obesity related disorders in some population. We evaluated Gln27Glu polymorphism in the β2AR gene in obese Saudi populations to investigate the association of β2AR gene with obesity and other related metabolic parameters.DesignWe studied possible association of Gln27Glu in β2AR gene with body mass index (BMI), anthropometric measurements and other metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…However, there were no differences in the genotype or allele frequency of the Gln and Glu variants in normal-weight, overweight, and obese individuals [28]. As a continuation of the earlier study we investigated the Arg/Gly polymorphism at position 16 in the β 2AR in the same Saudi cases and controls and our results show interesting associations.…”
Section: Discussionmentioning
confidence: 63%
“…However, there were no differences in the genotype or allele frequency of the Gln and Glu variants in normal-weight, overweight, and obese individuals [28]. As a continuation of the earlier study we investigated the Arg/Gly polymorphism at position 16 in the β 2AR in the same Saudi cases and controls and our results show interesting associations.…”
Section: Discussionmentioning
confidence: 63%
“…Catecholamines are regulators of lipolysis, and act via β1-, β2-, β3- (stimulatory), and α2- (inhibitory) adrenoceptor subtypes in adipose tissue. Most of the sympathetic nervous system-mediated energy expenditure in skeletal muscles takes place via the coupling of catecholamines with β2-adrenoceptors [ 15 , 16 ] and plays important roles in energy expenditure and control of body weight [ 9 17 ]. Recently, it has been shown that ARDBs are polymorphic with single nucleotide polymorphism (SNPs) exerting functional consequences affecting receptor activity and regulation, and hence may contribute to the pathophysiology of obesity and related disorders [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the sympathetic nervous system-mediated energy expenditure in skeletal muscles takes place via the coupling of catecholamines with β2-adrenoceptors [ 15 , 16 ] and plays important roles in energy expenditure and control of body weight [ 9 17 ]. Recently, it has been shown that ARDBs are polymorphic with single nucleotide polymorphism (SNPs) exerting functional consequences affecting receptor activity and regulation, and hence may contribute to the pathophysiology of obesity and related disorders [ 7 9 ]. Several studies have shown an association between ADRB polymorphism and BMI, T2DM, hypertension [HT] and dyslipidaemias, while other studies have failed to show such an association [ 18 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin stimulates glucose uptake through activation of adenosine monophosphate-activated protein kinase (AMPK). However, at high concentrations, it may inhibit AMPK activation, because it increases insulin receptor substrate-1 expression, due to the activation of the suppressor of cytokine signalling 3 46 . In the present study, these effects may be associated with the reductions in FM observed after the intervention, which consequently led to an improvement of the inflammatory status and of insulin response.…”
Section: Discussionmentioning
confidence: 99%